Research and progress in incremental sheet forming processes - Echrif, Salah B. M.; Hrairi, Meftah (Taylor & Francis, 2011)
Incremental sheet forming (ISF) is an emerging metal-forming technology in which the tool motion is controlled numerically. The process is economical to form complex parts in small to medium batches and provides a short and inexpensive way of forming products having a relatively simple but interesting shape. In this article, a review of the present state-of-the-art technologies and the potential applications of incremental sheet metal forming are presented in brief. This article seeks to address the approaches and methods that are prevalently applied. Furthermore, the article also seeks to guide researchers for future work, by identifying inadequacies of the current approaches and potential for valuable contributions in the field of incremental forming.